Interannual variation of summer sea surface temperature in the Amundsen Sea, Antarctica - Yu, Lu-Sha; He, Hailun; Leng, Hengling; Liu, Hailong; Lin, Pengfei (Frontiers in Marine Science, 2023)
This paper investigates the interannual variability of January sea surface temperature (SST) in the Amundsen Sea (AS) during the period 1982–2022. SST in the Pine Island Bay (PIB) is found to exhibit the most significant interannual variation, with a standard deviation up to 0.6°. Composite analysis indicates that, in warmer years, the January SST at PIB is approximately 1° higher on average than that in cooler years, and its variation in warmer (cooler) years corresponds to lower (higher) sea ice concentration (SIC) and more (less) surface heat flux; the latter factor is primarily influenced by the albedo of SIC. Further analysis suggests that variability in January SIC is largely dominated by northward sea ice motion during the previous November (r = −0.82), which is consistent with the presence of a contemporaneous northerly 10 m wind anomaly trigged by the Amundsen Sea Low (ASL). The ASL-associated northerly wind anomaly drives northward sea ice motion, reduces SIC, and thus increases the downward heat flux that ultimately results in warmer SST, and vice versa. This study identifies the possible mechanism of anomalous January SST in the PIB, which could provide an important clue for seasonal forecasts of summer SST in the AS.